Longitudinal Data Analysis - Fitzmaurice, Garrett, editor; Davidian, Marie, editor; Verbeke, Geert, editor; Molenberghs, Geert, editor (Boca Raton : Chapman and Hall/CRC, 2008)
Includes bibliographical references and index.